Архів Оперативного штабу Розенберга як джерело з історії використання нацистськими установами документальної спадщини народів окупованих країн Східної Європи - Кашеварова, Н. (Архіви України, 2009)
Article is dedicated to the studies of how archives and libraries that were confiscated by the Einsatzstab Reichsleiter Rosenberg from occupied Eastern European countries were used by the various Nazi organizations, high education institutions and societies with goals of propaganda and use of such resources to benefit Nazi Germany.